Two neutrophil populations in human blood with different chemotactic activities: separation and chemoattractant binding. - Harvath, L (Infect Immun, 1982)
Normal human blood contains a population of neutrophils that migrates to various chemoattractants and a population that fails to migrate. The percentage of neutrophils migrating to optimal concentrations of chemoattractants was quantified: 20 to 40% migrated to N-formylmethionyl-leucyl-phenylalanine, 30 to 50% migrated to human C5a, 25 to 35% migrated to human leukocyte-derived chemotactic factors, 20 to 30% migrated to casein, 15 to 20% migrated to pepstatin, and 1 to 5% migrated to medium alone. Neutrophil migration to the most active chemoattractant was not increased when other chemoattractants were added, indicating that the population of neutrophils migrating to the most active attractant was the same population that was migrating to the other attractants. The percentage of neutrophils migrating to a chemoattractant was not altered by prolonging the assay incubation period or by replacing the attractant with new chemoattractant during the assay, and the percentage was independent of the neutrophil concentration added to the chemotaxis chamber. Nonmigrating neutrophils were isolated with a chemotaxis collection chamber, and they were examined for radiolabeled chemotactic peptide binding. The binding of radiolabeled N-formylmethionyl-leucyl-phenylalanine by nonmigrating and migrating neutrophils was identical.